1990
DOI: 10.1177/036354659001800210
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an iliotibial tenodesis on intraarticular graft forces and knee joint motion

Abstract: Lateral extraarticular reconstructions are used as isolated procedures in knees with moderate rotatory instability and as "backups" in knees requiring primary repair or intraarticular reconstruction for major rotatory instability. We used an experimental knee testing system to analyze the immediate postoperative mechanical effect of an iliotibial band tenodesis on an intraarticular reconstruction of the ACL in fresh cadaver knees using a composite graft consisting of a bone-patellar tendonbone segment augmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
189
0
4

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(200 citation statements)
references
References 16 publications
7
189
0
4
Order By: Relevance
“…Some ACL injuries may be more complex than previously believed, and a combination of central and peripheral structures appear to be involved in the pathoanatomy of pivot shift injury. Previous studies also have shown that the addition of an extraarticular lateral restraint can decrease rotational instability, as assessed by the pivot shift test [12,13,24]. Understanding the improved Lachman test results among patients who underwent combined ACL reconstruction is less straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Some ACL injuries may be more complex than previously believed, and a combination of central and peripheral structures appear to be involved in the pathoanatomy of pivot shift injury. Previous studies also have shown that the addition of an extraarticular lateral restraint can decrease rotational instability, as assessed by the pivot shift test [12,13,24]. Understanding the improved Lachman test results among patients who underwent combined ACL reconstruction is less straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of stability can be due to the protective effect of the anterolateral structure on the intra-articular reconstruction, particularly during its phase of healing [4,6,18]. This extra-articular procedure seems to be useful in cases of serious and chronic instability, when the secondary restraints have become stretched.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analysis performed by Engebretsen et al [14] have shown that the extra-articular plasty, when used in combination with intra-articular reconstruction, reduces the stress on the graft by approximately 43%. Bignozzi et al [15•] also showed by navigation in their "in vivo" study that the addition of an extra-articular tenodesis to single-bundle ACL reconstruction may be effective in controlling coupled tibial translation during the Lachman test and in reducing anteroposterior laxity at 90°of flexion.…”
Section: Discussionmentioning
confidence: 99%